Britain and China - Luard, Evan (Johns Hopkins University Press, 2019)
Originally published in 1962. This book is a study of relations between Britain and China. The first section surveys historical relations between the two nations and culminates with the Second World War. The second part examines British policy during the Chinese Civil War, the Korean War, and the Geneva Conference. The third part discusses what contemporary issues in British-Chinese relations were at the time the book was written.